QUANTITATIVE HISTOPATHOLOGICAL ANALYSIS OF ENLARGED CELLS DERIVED FROM HUMPBACK GROUPER, Cromileptes altivelis INFECTED WITH GROUPER SLEEPY DISEASE IRIDOVIRUS (GSDIV) - Indah Mastuti; Yasmina Nirmala Asih; Ketut Mahardika (Indonesian Aquaculture Journal, 2010)
Pathognomonic sign of grouper sleepy disease iridovirus (GSDIV) was proposed to be the formation of enlarged cells and necrotic cells, in which under electron microscope, it is revealed to be the inclusion body bearing cells (IBCs) and necrotic cells containing GSDIV viral particles. Spleen and kidney tissues are the major sites for formation of enlarged cells. This paper described the result of histopatological analysis of enlarged cells found in the spleen and kidney of moribund fish after GSDIV challenge. A pathogenicity test was conducted on fish stocked in two tanks for infected groups and the other two tanks for uninfected control groups (15 fish per tank). The infected groups were injected intramuscularly with 0.1 ml of the viral inoculum. The uninfected groups were injected with the same amount of EMEM-2. The GSDIV-infected humpback grouper began to die after 6 days post infection and all died after 7 dpi, excluding one fish which had survived until the end of experimental infection periods (93% to 100% mortality). All of the diseased fish showed massive formation of enlarged cells in their spleen, head kidney and trunk kidney. The largest number of enlarged cells was observed on head kidneys and subsequently followed by spleens, trunk kidney (2.0-200.3/field of view). This result suggested that the number of enlarged cells in the affected organs was not the direct factor that led to the mortality of fish.